Stalinism and Nazism : dictatorships in comparison - Kershaw, Ian 1943- Hrsg; Lewin, Moshe 1921-2010 Hrsg (Cambridge Univ. Press, 1997)
Introduction: The regimes and their dictators: perspectives of comparison / Ian Kershaw, Moshe Lewin -- Stalin and his Stalinism: power and authority in the Soviet Union, 1930-53 / Ronald Grigor Suny -- Bureaucracy and the Stalinist state / Moshe Lewin -- Cumulative radicalisation and progressive self-destruction as structural determinants of the Nazi dictatorship / Hans Mommsen -- 'Working towards the Fuhrer': reflections on the nature of the Hitler dictatorship / Ian Kershaw -- Stalin in the mirror of the other / Moshe Lewin -- The contradictions of continuous revolution / Michael Mann -- From Blitzkrieg to total war: controversial links between image and reality / Omar Bartov -- Stalin, the Red Army, and the "Great Patriotic War' / Bernd Bonwetsch -- The economics of war in the Soviet Union during World War II / Jacques Sapir -- From 'Great Fatherland War' to the Second World War: new perspectives and future prospects / Mark von Hagen -- German exceptionalism and the origins of Nazism: the career of a concept / George Steinmetz -- Stalinism and the politics of post-Soviet history / Mark von Hagen -- Work, gender and everyday life: reflections on continuity, normality and agency in twentieth-century Germany / Mary Nolan -- Afterthoughts / Ian Kershaw, Moshe Lewin